Proses Rekruitmen Guru Di SDIT Nur Hidayah Surakarta - Siskasari, Fitri (2016)
Fitri Siskasari/A510120218. TEACHER RECRUITMENT IN NUR HIDAYAH ISLAMIC PRIMARY SCHOOL (SDIT) SURAKARTA. Skripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Maret, 2016. Recruitmen of teacher is one of the factors supporting the succes of an educational institution. Qualified teachers can be gained through good recruitment process. In these conditions the recruitment team in SDIT NUR Hidayah Surakarta tries to roduce of good quality teachers. The purpose of this study is to describe the management of teacher recruitment in SDIT Nur Hidayah of Surakarta that produces good quality teachers. This research used descriptive qualitative approach. The implementation of this research was 4 month beginning from November until February 2015-2016. Object of this research was SDIT Nur Hidayah of Surakarta. The informants of this reseaerch were chief of intitution, principal, teachers, and administration officers. Data collecting method applied observation, interview, and documentation, while, data validation techniques used triangulation method and sources. Technique of data analysis used interacrive model consisting of data collecting, reduction, performing, and verification.Research result show that recruitment of new teachers in SDIT Nur Hidayah Surakarta regency provides good quality of new teachers. The purpose of recruitment can be achieved bacause recruitment of new teaches has been done well, including: a) planning of new teacher's recruitment by analyzing of teacher's needs, b) organizing has been done by the making a special team in new teacher's recruitment, c) executing of recruitment including socialization announcement of new teacher's acceptance, administration selection, writing, interview, reading and memorizing of Qur'an, and microteaching tests, d) controlling of recruitment by school party has been done effectively. In this matter, it can be seen in new teacher's recruitment process whit has been done by recruitment team sekectively and systematically, therefore, it provides the qualified teachers. Key word: implementation of recruitment, teacher.